POTENSI CULTURAL LANDSCAPE UNTUK PENGEMBANGAN ATRAKSI WISATA DI DESA BONGKASA PERTIWI, BALI - ANAK AGUNG BAGUS BAYU ANGGAWIRYA; KADEK PUTRA SANTIKA NARAYANA (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to identify the potential of the cultural landscape in Bongkasa Pertiwi Village, Badung Regency, Bali, and how these elements can be developed into sustainable tourist attractions. Bongkasa Pertiwi Village has various rich cultural landscape elements, such as rice fields with subak irrigation systems, temples, and springs (beji), which have not been optimally utilized as tourist attractions. Observations and data analysis were carried out by dividing the village area into three village area segments to evaluate the development potential and existing challenges. The results of the study show that: Segments 1 and 2 are dominated by rice field cultural landscapes, and there are springs (beji) and temples Segment 2, while Segment 3 is dominated by tourist attractions and residential areas where there is no cultural landscape whose potential has not been utilized The obstacles faced develop cultural landscapes as tourist attractions are limited infrastructure and lack of measurable data on cultural landscape elements in Bongkasa Pertiwi Village.